The New New Product Development Game - Takeuchi, Hirotaka; Nonaka, Ikujiro (Harvard Business Review, 1986)
In today’s fast-paced, fiercely competitive world of commercial new pr oduct development, speed and flexibility are essential. Companies are increasingly realizing that the old, sequential approach to developing new products simply won’t get the job done. Instead, companies in Jap an and the United States are using a holistic method—as in rugby, the ball gets passed within […]